Sunlight exposure practice and its associated factors among infants in Ethiopia, systematic review and meta-analysis. - Fanos Yeshanew Ayele; Natnael Kebede; Asnakew Molla Mekonen; Mengistu Mera Mihiretu; Yawkal Tsega; Elsabeth Addisu; Niguss Cherie; Tesfaye Birhane; Chala Daba; Ahmed Hussien Asfaw; Zinet Abegaz; Abel Endawekie; et al. (PLoS ONE)
Background Lack of sunlight exposure is the primary reason for the worldwide epidemic of vitamin D deficiency. There was a meta-analysis conducted under the title of Knowledge and Practice of Mothers towards sunshine exposure of their children in Ethiopia. However, studies conducted on factors associated with sunlight exposure practice among infants showed non-conclusive and inconsistent findings. Hence, this systematic review and meta-analysis were conducted to estimate the pooled prevalence of good sunlight exposure practice and its associated factors among infants in Ethiopia. Methods All articles were systematically searched by PubMed, Hinari, Global Health and CINAHL, Epistemonikos, African Journal of Online (AJOL), Google Scholar and Google. All studies, until the end of May 30, 2023, were included in this review. Pure qualitative studies and studies in which the outcome was not reported were excluded from the review. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses guideline was used. Meta-analysis was conducted by using STATA 17 software. Forest plots were used to present the pooled prevalence of good sunlight exposure practices. A random effect model was used to compute the pooled prevalence, while subgroup analysis was performed to identify the possible source of heterogeneity. Publication bias was assessed by begg's and Egger's tests. We use Trim and fill analysis was used to treat the publication bias. Results This review involved 14 studies and 6,121 participants. The pooled prevalence of good sunlight exposure practice among infants in Ethiopia was 53.46% (95%CI: 45.98, 60.95). Mothers had PNC follow-up [OR = 2.22 (95% CI: 1.31, 3.47)], mothers with secondary and above educational status [OR = 4.17, (95% CI: 1.73, 10.06)], employed mothers [OR = 3.72, (95% CI: 2.71, 5.11)], urban residence [OR = 2.67, (95% CI: 1.17, 6.08)] and not fear of sunlight exposure [OR = 4.08, (95% CI: 1.44, 16.00)] were positively associated with good sunlight exposure practice. Conclusions The pooled prevalence of good sunlight exposure practices among infants in Ethiopia is low. Had postnatal care follow-up, being urban residents, mother's employment status, mother's educational status and not fear of sunlight exposure were independent factors of good sunlight exposure practice among infants. Therefore, health professionals create awareness for mothers to increase postnatal follow-up, and the importance of health education especially for rural residents.